Corn Ethanol and U.S. Biofuel Policy 10 Years Later: A Quantitative Assessment. (13th February 2018) - Hochman, Gal; Zilberman, David
Abstract: We conduct meta‐analyses of the estimated impacts of corn ethanol on food and fuel prices, as well as greenhouse gases, and analyze the implications for the balance of trade. The meta‐analyses suggest that corn ethanol has minor effects on greenhouse gas emissions and significant yet moderate effects on food and fuel prices. However, corn ethanol has a relatively significant impact on fuel security in terms of reductions in the import of oil to the U.S. and its overall effect on the U.S. balance of trade.